2007
DOI: 10.1177/152692480701700307
|View full text |Cite
|
Sign up to set email alerts
|

In My Shoes: Children's Quality of Life after Heart Transplantation

Abstract: The children described their quality of life as "mostly good," yet reported that life was "easy and not easy." Ten factors that affected the children's quality of life were Doing Things/Going Places, Favorite School Activities, Hard Things About School, Being With Friends and Family, Doing Things/Going Places With Friends and Family, Interactions With Friends and Family, Taking Care of My Heart, My Body, The Transplant Team, and Other Health Problems. Based on similarities in meaning, these factors were combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…One qualitative study found that pediatric cardiac transplantation patients described their lives as ‘mostly good' or ‘fun' and noted that they valued the normal aspects of life (110). Another study reported that the majority (78%) of patients exhibited improved psychological functioning after cardiac transplantation, which was maintained after a decade.…”
Section: Introductionmentioning
confidence: 99%
“…One qualitative study found that pediatric cardiac transplantation patients described their lives as ‘mostly good' or ‘fun' and noted that they valued the normal aspects of life (110). Another study reported that the majority (78%) of patients exhibited improved psychological functioning after cardiac transplantation, which was maintained after a decade.…”
Section: Introductionmentioning
confidence: 99%
“…The physical improvements afforded by transplant, and corresponding sense of freedom, are likely to be an important mechanism through which the increased quality of life that is observed in the literature occurs. Indeed, the ability to take part in desired activities, spend time with friends, and live a "normal" life are benefits that have been cited by other qualitative studies of life after transplant (6,39,40). Furthermore, it appears that the adolescents' improved physical functioning impacted upon their developmental trajectory, bringing their level of autonomy and independence in line with what would be expected for young people of their age.…”
Section: Discussionmentioning
confidence: 91%
“…As nursing practice has expanded so have the research methods used to study the meanings of health, illness, nursing, and culture (Roper & Shapira, 2000;Streubert & Carpenter, 2011). Nurses have used ethnography to study the nature of attachment in a NICU (Bialoskurski, Cox, & Hayes, 1999), cancer units (Germain, 1979), and children's quality of life after heart transplantation (Green, McSweeney, Ainley, & Bryant, 2007). Because ethnography is an approach to understanding human behavior, nursing research of nursing practice helps nurses to understand specific cultures of healthcare.…”
Section: Ethnographymentioning
confidence: 99%